Dielectric properties and conductivity of PVdF-co-HFP/LiClO4 polymer electrolytes - TAV, CUMALİ; YAHŞİ, UĞUR (CANADIAN SCIENCE PUBLISHING, NRC RESEARCH PRESS, 2018)
In this study, it was aimed to prepare a series of PVdF-co-HFP based electrolytes with different LiClO4 loadings and to investigate their chemical and electrical properties in detail. For this purpose, PVdF-co-HFP based electrolytes with different LiClO4 loadings (1-20 weight %) were prepared using solution casting method. X-ray diffraction (XRD), differential scanning calorimetry, and thermogravimetric (TGA)-differential thermal and dielectric spectroscopy analysis of PVdF-co-HFP/LiClO4 were performed to characterize their structural, thermal, and dielectric properties, respectively. XRD results showed that the diffraction peaks of PVdF-co-HFP/LiClO4 electrolytes broadened and decreased with LiClO4. TGA patterns exhibited that PVdF-co-HFP/LiClO4 electrolytes with 20 wt % of LiClO4 had the lowest thermal stability and it degraded above 473 K, which is highly applicable for solid polymer electrolytes. Dielectric constant, dielectric loss, and conductivities were calculated by measuring capacitance and dielectric loss factor of PVdF-co-HFP/LiClO4 in the range from 10 mHz to 20 MHz frequencies at room temperature. In consequence, conductivities of PVdF-co-HFP/LiClO4 increased significantly with frequency for low loading of LiClO4 while they only slightly changed with higher LiClO4 addition. On the other hand, dielectric constant values of PVdF-co-HFP/LiClO4 films decreased with frequency whereas they rose with LiClO4 addition. The dielectric studies showed an increase in dielectric constant and dielectric loss with decreasing frequency. This result was attributed to high contribution of charge accumulation at the electrode-electrolyte interface. The electrolyte showed the maximum conductivity of 8 x 10(-2) S/cm at room temperature.
Keywords: conducting polymers; impedance spectroscopy; dielectric properties; ionic conductivity; LITHIUM SALT CONCENTRATION; IONIC-CONDUCTIVITY; RELAXATION; PERCHLORATE